A dangerous science: psychology in Al Qaeda's words. Issue 1 (2nd January 2018) - Grace, Emma
Abstract: Terrorist organizations' use of psychology in analysing psychological issues in the everyday lives of their members and developing coping strategies has not been sufficiently investigated in the terrorism research. This qualitative study investigates Al Qaeda's view of psychology, its analysis of psychological issues, and the utilization of coping strategies among terrorists. The study is based on 255 documents from the Bin Laden's Bookshelf (Office of the Director of National Intelligence. [2015]. Bin Ladin's Bookshelf. Retrieved fromhttps://www.dni.gov/index.php/features/bin-laden-s-bookshelf ) and Harmony database documents (The Combating Terrorism Center at West Point [CTC]. [2012]. Harmony program. Retrieved fromhttps://ctc.usma.edu/programs-resources/harmony-program ). The results indicate that Al Qaeda perceived psychology as a dangerous and important science. Psychological issues identified in this study include three types of suicide, depression, anxiety, security stress, diversity stress, and enforced idleness. Terrorists used both religious and secular coping strategies to overcome psychological issues. These findings can contribute to future research and counterterrorism efforts in understanding both the survivability and vulnerability of terrorists.